Demands, default options and definitions: How artefacts mediate sustainability in public housing projects in Sweden and Cyprus. (October 2022) - Francart, Nicolas; Polycarpou, Kyriacos; Malmqvist, Tove; Moncaster, Alice
Abstract: Sustainable building design practices are influenced by requirements, guidelines, criteria for green procurement and certification, assessment tools such as life cycle assessment, etc. This study investigates how such artefacts support or define aspirations towards sustainability, through case studies of public housing projects in Sweden and Cyprus. The study first illustrates how constraints mediated by artefacts set boundaries to the range of available sustainable design options. On one hand, fulfilling sustainability requirements conveyed in regulations, certifications and directives is a major driver of designers' involvement with sustainable design. On the other hand, cost calculations, procurement laws and development plans exclude certain design options. Moreover, default solutions and standardised design guidelines within the organisation streamline and simplify the design process, indirectly determining what sustainable design options are considered. However, these demands and default options are also bent and adapted on a case-by-case basis. The ways in which sustainable design arises from the interplay between artefacts and actors' agency differed significantly between the Swedish and Cypriot cases. Swedish actors' operational definition of sustainability is strongly codified and enforced through interconnected artefacts. The Miljöbyggnad certification is often a de facto definition of sustainability used by actors to set sustainability criteria and targets. Environmental databases for construction products act as black boxes, implicitly determining what aspects of sustainability are addressed in design decisions. Conversely, Cypriot designers' work with sustainability depends to a larger extent on their motivation, experience and ability to convince their peers. Highlights: Regulations, directives and certifications frame the range of design choices. Key design choices are often taken outside the project, at the level of the organisation. Certifications and tools 'black-box ' and operationalise the notion of sustainability. Sustainable design is strongly affected by the (often unintended or invisible) impact of artefacts. The impact of artefacts on the design process differs between national contexts.